Catalase‐Like Nanozymes: Classification, Catalytic Mechanisms, and Their Applications. Issue 37 (15th August 2022) - Xu, Deting; Wu, Liyuan; Yao, Haodong; Zhao, Lina
Abstract: The field of nanozymes has developed rapidly over the past decade. Among various oxidoreductases mimics, catalase (CAT)‐like nanozyme, acting as an essential part of the regulation of reactive oxygen species (ROS), has attracted extensive research interest in recent years. However, CAT‐like nanozymes are not as well discussed as other nanozymes such as peroxidase (POD)‐like nanozymes, etc. Compared with natural catalase or artificial CAT enzymes, CAT‐like nanozymes have unique properties of low cost, size‐dependent properties, high catalytic activity and stability, and easy surface modification, etc., which make them widely used in various fields, especially in tumor therapy and disease treatment. Consequently, there is a great requirement to make a systematic discussion on CAT‐like nanozymes. In this review, some key aspects of CAT‐like nanozymes are deeply summarized as: 1) Typical CAT‐like nanozymes classified by different nanomaterials; 2) The catalytic mechanisms proposed by experimental and theoretical studies; 3) Extensive applications in regard to tumor therapy, cytoprotection and sensing. Therefore, it is prospected that this review will contribute to the further design of CAT‐like nanozymes and optimize their applications with much higher efficiency than before. Abstract : The catalase‐like nanozyme has attracted extensive interest in recently years due to its excellent properties of high catalytic activity and stability. In this review, systematic organization of their classifications, catalytic mechanisms, and applications are made, which are expected to provide valuable ideas for the rational design and optimal applications of nanozymes in the future.